Chemical attrabutes of soil organic fertilizer on systems of coffee conilon - Maurício da Silva, Victor; Rabelo Teixeira, Alex Fabian; Fialho dos Reis, Edvaldo; Benassi, Antônio Carlos; de Sá Mendonça, Eduardo (Coffee Science - ISSN 1984-3909, 2014)
The production of Conilon in organic systems has increased in the state of Espírito Santo, however, information on the impact of management on soil chemical characteristics are few and inconclusive. The aim of this study was to evaluate the effect of organic management fertilization on chemical properties of soil in agroecossystem conilon. On a farm in the municipality of Linhares, state of Espirito Santo, was mounted experiment in randomized complete block design with factorial distribution 2 x 2 x 5, with three replications, with factors: two organic compounds, presence and absence of legumes and five proportions of each compound (0, 25, 50, 75, and 100%) in replacement of mineral fertilization recommended. Each replication consisted of a plot of 30 plants of coffee, with 12 working stations. The compounds were: compound 1, prepared with elephant grass and straw-de-café in the ratio 1:1 (v: v) and compound 2, prepared with elephant grass thatched-of-coffee and bed-ofchicken in the ratio 2:1:1 (v: v: v). The legume used was the bean-to-pig, sown between the rows of coffee trees. With the use of 100% of compound 1 and compound 2, the pH reached values of 6.5 and 6.3 respectively compared to pH 4.8 obtained with the mineral fertilizer. he means for the sum of bases (SB) followed the behavior of the exchangeable cations (Ca, Mg and K) of the soil that is linearly increased (p <0.10) with increasing proportions of the compounds. The fertilization with organic compounds is an alternative to improve soil fertility in agroecosystems of conilon.